Double-diffusive convection in compressible fluids with suspended particles in porous medium (Archives of Mechanics - Test, 1996)
The double-diffusive convection in compressible fluids with suspended particles in porous medium is considered. The suspended particles are found to have destabilizing effect whereas stable solute gradient, rotation and compressibility have stabilizing effect on the system. The medium permeability has a destabilizing effect in the absence of rotation but has both stabilizing and destabilizing effects in the presence of rotation. The stable solute gradient and rotation are found to introduce oscillatory modes in the system which are non-existent in their absence.